Cities as innovation poles in the digital transition. The Italian case - Giuseppe Borruso; Ginevra Balletto (AIMS Geosciences)
Since the beginning of settled civilizations, cities have represented places of innovation and meeting points for flows of goods, services, people, ideas, and cultural expressions. Cities as places of interaction help to develop new ideas, solutions, and applications. If the spreading of innovation in the past appeared as a spontaneous process, nowadays it is inserted into more structured business models for enterprises and companies and in development policies at central, regional, and local levels. This also involves cities, as investing in innovation can represent opportunities for their growth. Urban geography literature, for instance, examines the urban life cycle, which has evolved into what Florida terms the 'New Urban Crisis'. Based on the 'demographic winter' facing Italy and other industrialized countries, the present work aims to observe the most recent urban dynamics in spatial and demographic changes, innovation, and digital transitions. This research combined an analysis of innovative cities in Italy, based on the innovation index (ICity Rank) with demographic data, considering metropolitan cities and their functional urban areas (FUAs), along with a set of mid-sized cities identified as 'innovative' and dynamic. Cities were ranked within the urban life cycle model, employing LISA (Local Moran's I) as a method for analysis and clustering. Using spatial analytical techniques, the work focused on the Italian urban system, its capital cities and mid-size innovative cities, considering urban dynamics in terms of population change, income, and innovation, observing their characteristics and recent evolution (2019–2023). The findings highlight the formation of urban 'champions' and their characteristics in terms of ability to attract people and expertise. The results show that innovative metropolitan cities are able to maintain population levels, particularly in suburban rings, while populations in the core areas tend to decline. However, certain innovative metropolitan cities in Southern Italy maintained or increased the core population. In general, medium-sized cities present more interesting dynamics, showing either population stability or a slower rate of decline.